KINERJA PEGAWAI TERHADAP PELAYANAN PEMELIHARAAN KESEHATAN MASYARAKAT SURAKARTA (PKMS) DI PUSKESMAS JAYENGAN KOTA SURAKARTA - Liliek Winarni & Wahyu Bhudianto, Nur Aini Yulianti (Transformasi, 2014)
Employee performance on Community Health Services Surakarta (PKMS) is the performance of employees in providing services to patients PKMS must serve with Standard Operational Procedure (SOP) for the patient satisfied with the services provided. Therefore, when viewed from several performance indicators, namely accountability, responsibility, orientation to the task, and the service quality is good. But for employees is still low responsiveness in addressing the many issues queue of patients. Keywords : performance, service, healthy